MEX3A is a diagnostic, independent prognostic biomarker and a promising therapeutic target in glioblastoma - Bufalieri, Francesca; Armocida, Daniele; Cucinotta, Antonino; Familiari, Pietro; Di Magno, Laura; Serraino, Alessandra; Adabbo, Gennaro; Agnoli, Francesca; Lospinoso Severini, Ludovica; Antonelli, Manila; Frati, Alessandro; Canettieri, Gianluca; et al. (Frontiers in Oncology, 2025)
ObjectiveGliomas are the most common malignant brain tumors with a poor prognosis. Despite advances in molecular profiling, no targeted therapies significantly improve survival. Recently, it has been demonstrated that high expression of Muscle Excess 3A (MEX3A) correlates with poor overall survival (OS) in gliomas, generating interest in its potential as a biomarker and therapeutic target. This study analyzes the correlation between MEX3A expression and clinical-molecular features, assessing its diagnostic, prognostic, and therapeutic value in glioblastoma (GB), the most aggressive glioma subtype.MethodsWe performed a retrospective study on a consecutive series of surgically-treated glioma patients. The values of MEX3A mRNA levels for the discrete variables examined has been reported by boxplots. Chi-square tests were carried out to analyze the correlation between MEX3A expression and patient features. Receiver operating characteristic (ROC) curve, Kaplan-Meier survival and Cox regression analysis were applied to assess the diagnostic and independent prognostic values of MEX3A in GB. Finally, the effect of MEX3A genetic knockdown on human primary GB both in vitro and in vivo orthotopic xenograft model cell has been evaluated.ResultsElevated MEX3A expression associates with more severe clinicopathological and molecular features of glioma patients. MEX3A exhibits high diagnostic accuracy (AUC > 0.9) and correlates with poor OS (HR=2.068, p=0.0018) and progression-free survival (PFS) (HR=2.209, p=0.0005) in GB. Multivariate Cox regression identified MEX3A as an independent prognostic factor for OS and PFS. Notably, MEX3A knockdown inhibits tumor growth in vitro and in vivo.ConclusionsOur findings highlight MEX3A as a novel diagnostic and prognostic biomarker and a promising therapeutic target for GB.